Effectiveness of group discussion with assertive training in enhancing generation z self-confidence in senior high school - Aep Saepuloh; Mumu Muzayyin Maq; Dhita Jala Samudera; Elsya Eliasari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study was motivated by the low level of self-confidence among Generation Z, which may influence students’ personal and social development within theschool environment. The purpose of this study was to examine the effectiveness of group discussion services using the assertive training technique in improving the self-confidence of Generation Z students in SMA Negeri Kota Cirebon. This research employed a quantitative approach with a One-Group Pretest–Posttest experimental design. The research subjects consisted of 52 students from public SMA Negeri Kota Cirebon who were selected as participants in the group discussion sessions. Data were collected using a self-confidence scale administered before the treatment (pretest) and after the treatment (posttest). The data were analyzed using statistical tests to examine the differences between the pretest and posttest scores. The results indicated a significant difference between students’ self-confidence scores before and after the implementation of group discussion with the assertive training technique. This finding was supported by a significance value of 0.000 < 0.05, indicating that H0 was rejected and H1 was accepted. Therefore, group discussion services with the assertive training technique are effective in enhancing the self-confidence of Generation Z students.